H3N2 Emergence in India - Ramachandran, Smita; Gera, Rani (International Journal of Pediatrics and Child Health, 2015)
Influenza a pandemic in 2009 was predominantly by H1N1strain, however in the current seasonal outbreak H3N2 is more prevalent in North America, Europe and Eastern Asia. However very few cases have been reported from India. We report a case of 5-year-old girl child with H3N2 infection with acute onset and rapid progression. It is essential to deploy extensive surveillance in areas of low reporting to estimate the burden of the disease and to assess the changing demographics of the infection.